2007
DOI: 10.1021/bi7013272
|View full text |Cite
|
Sign up to set email alerts
|

CGFS-Type Monothiol Glutaredoxins from the Cyanobacterium Synechocystis PCC6803 and Other Evolutionary Distant Model Organisms Possess a Glutathione-Ligated [2Fe-2S] Cluster

Abstract: When produced in Escherichia coli, the CGFS-type monothiol Grxs from this organism (EcGrx4p) and the model cyanobacterium Synechocystis (SyGrx3p) exist as a dimeric iron-sulfur containing holoprotein or as a monomeric apoprotein in solution. Spectroscopic and site-directed mutagenesis analyses show that the SyGrx3 holoprotein contains a subunit-bridging [2Fe-2S] cluster that is ligated by the catalytic cysteine located in the CGFS motif of each monomer and the cysteines of two molecules of glutathione. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
153
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(168 citation statements)
references
References 30 publications
15
153
0
Order By: Relevance
“…The yeast GRX proteins Grx3/4 and the mammalian ortholog GRX3/PKC-interacting cousin of TRX (PICOT) have been associated with the CIA pathway and contain themselves [2Fe-2S] clusters (Picciocchi et al, 2007;Haunhorst et al, 2010). Deletion of Grx3/4 in yeast leads to defects in cytosolic and mitochondrial Fe-S assembly, deregulation of iron homeostasis, and defects in proteins containing di-iron centers (Mühlenhoff et al, 2010).…”
mentioning
confidence: 99%
“…The yeast GRX proteins Grx3/4 and the mammalian ortholog GRX3/PKC-interacting cousin of TRX (PICOT) have been associated with the CIA pathway and contain themselves [2Fe-2S] clusters (Picciocchi et al, 2007;Haunhorst et al, 2010). Deletion of Grx3/4 in yeast leads to defects in cytosolic and mitochondrial Fe-S assembly, deregulation of iron homeostasis, and defects in proteins containing di-iron centers (Mühlenhoff et al, 2010).…”
mentioning
confidence: 99%
“…As reported for several ISC-glutaredoxin complexes (6,25,40,42,43,54,67,75), most probably two GSH molecules act as the low molecular mass ligands of the ISC in the holo-form of the trypanosomal proteins extracted from E. coli. In vitro reconstitution of the iron-sulfur proteins in the presence of Gsp or T(SH) 2 revealed that these parasite specific thiols can easily substitute for GSH as the nonprotein ligand(s).…”
Section: -C-grxs As Well As 2-c-grx1 Are Capable Of Binding An Ironsmentioning
confidence: 62%
“…Except for yeast Grx6 and Grx7 (59,60), most 1-C-Grxs lack or have negligible classical disulfide reductase activity (18,26,27,43,69,82). Instead, the capability to coordinate ISCs appears to be a common feature for 1-C-Grxs (16,40,42,43,54,67,89) with yeast Grx7 being, so far, the only known exception (59,60). The latter feature determines an evolutionary conserved and indispensable role of 1-C-Grxs in the biogenesis and assembly of iron-sulfur proteins (11,61) and other cell-specific regulatory functions such as the (in)activation of nuclear transcription factors (35,62,86).…”
Section: Fig 2 Sequence Analysis Of Monothiol Glutaredoxins (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently glutathionylation was reported to regulate the activity of two proteins from Synechocystis 6803 [88,89]. Synechocystis 6803 possesses only one monothiol [90] and two dithiol glutaredoxins (Grxs), which have been shown to specifically interact with various protein partners resistant to toxic metals and various other stresses [88,[91][92][93]. In addition, several targets of one dithiol Grx (Ssr2061) from Synechocystis have been identified by proteomic methods [94].…”
Section: Glutathionylomementioning
confidence: 99%